Rwanda : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Nonobservance of Performance Criteria and for Extension of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2005)
The Fourth Review Under the Poverty Reduction and Growth Facility and Requests for Waiver of Nonobservance of Performance Criteria for Rwanda are analyzed. The implementation of policies improved considerably in 2004, although economic performance has been adversely affected by exogenous shocks. Strong activity in construction, transport, and communication raised growth to 4 percent, despite major electricity shortages. Macroeconomic and structural policies will aim at enhancing private sector development and accelerating productivity-enhancing strategies. Fiscal policies will focus on supporting macroeconomic stability and improving the quality of spending through a sizable reallocation to priority areas.